2019
DOI: 10.1590/s0004-2803.201900000-53
|View full text |Cite
|
Sign up to set email alerts
|

Different Scoring Systems in Acute Alcoholic Pancreatitis: Which One to Follow? An Ongoing Dilema

Abstract: BACKGROUND: Acute pancreatitis is a common disorder in medical practice. In recent times, management has changed drastically with majority of decisions like intravenous antibiotics, negative suction with Ryle’s tube and surgical interventions like necrosectomy etc based on severity of the disease. There are different scores in use to assess severity of disease but the relative efficacy has remained a debatable subject. OBJECTIVE: The present study was thus done to investigate the predictive accuracy of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Table 1 presents a summary of relevant studies. The 43 studies 24–65 included 14,116 AP patients, with mean/median age ranging widely (35–72 years) as the rate of male patients (34%–86%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 presents a summary of relevant studies. The 43 studies 24–65 included 14,116 AP patients, with mean/median age ranging widely (35–72 years) as the rate of male patients (34%–86%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐four studies (79%) took place in Institutions in Asia, 24–28,30–35,37,39,41–52,54–56,58–62,65 7 in Europe, 36,38,40,53,57,63,64 2 in the USA 9,29 . Twenty‐one studies were prospective, 9,25,29,32–36,38,41,44,45,47,51–54,57,59,61,65 21 retrospective 24,26–28,30,31,37,39,40,42,46,48–50,55,56,58,60,62–64 and 1 cross‐sectional 43 . Three of the studies included both training and validation sets, 9,37,39 and one two cohorts of different age groups 50 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SAP can be diagnosed when patients had an APACHEⅡ score of > 8, and those patients need to be transferred to ICU [12]. Study had shown that APACHE II score is a reliable scoring system, and has high sensitivity for assessing the severity, organ failure and death in AP [13]. However, the APACHEⅡ score can only be determined after 24 hours of admission, and it is a complex system which includes many indicators, and highly depends on laboratory test results, so dynamic determination of disease severity is difficult.…”
Section: Discussionmentioning
confidence: 99%